Modification of the argon stripping target of the tandem accelerator. (December 2015) - Makarov, A.; Ostreinov, Yu.; Taskaev, S.; Vobly, P.
Abstract: The tandem accelerator with vacuum insulation has been proposed and developed in Budker Institute of Nuclear Physics. Negative hydrogen ions are accelerated by the positive 1 MV potential of the high-voltage electrode, converted into protons in the gas stripping target inside the electrode, and then protons are accelerated again by the same potential. A stationary proton beam with 2 MeV energy, 1.6 mA current, 0.1% energy monochromaticity, and 0.5% current stability is obtained now. To conduct Boron Neutron Capture Therapy it is planned to increase the proton beam current to at least 3 mA. The paper presents the results of experimental studies clarifying the reasons for limiting the current, and gives suggestions for modifying the gas stripping target in order to increase the proton beam current along with the stability of the accelerator.